Ženski glas hrvatskih petrarkista - Bogdan, Tomislav (Array, 2002)
Early Croatian Petrarchists adhere to the convention of the female voice. Their poems with an enamored feminine lyrical subject usually count on a realized love relationship, and the separation of the woman teller from the man is presented as more or less the result of objective circumstances. The feminine lyrical subjects show some reserve towards Petrarchistic discourse, notably towards its typical figures; their statements are in general less rich in figures and stylistically less competent than the masculine subjects’, and their forms of address are more conversational. By connecting the feminine with stylistic simplicity and the colloquial, male authors imply a whole range of cultural facts, among others that of female lack of education.